Reve Ta Stohne w trasie - Parfan, Nadia (Ukraine, 2016)
Aspiring musicians and bandmates Zhenia and Maks give up their office jobs to start Reve ta Stohne, a psychedelic, growl singing band that the boys hope will make them real rock stars. However, for a start they need a music video and a studio album. And most of all they need money to pay for them. In search of income, Reve ta Stohne travel from their native Ukraine to tour western europe.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films